2009
DOI: 10.1007/s11274-009-9996-3
|View full text |Cite
|
Sign up to set email alerts
|

Cometabolic degradation of mono-chloro benzoic acids by Rhodococcus sp. R04 grown on organic carbon sources

Abstract: The aerobic cometabolism of chlorobenzoic acids (CBAs) by Rhodococcus sp. R04 was accomplished by augmenting the medium with organic carbon sources. In mineral medium supplemented with glucose (MMG), 0.5 mM 2-CBA was incompletely metabolized after the 5-day incubation, while the near-complete disappearance of 0.5 mM 4-CBA was monitored. Over the 5-day incubation period, the concentration of chloride increased to 0.17 mM in bottles containing 4-CBA, glucose and strain R04; whereas in cultivation with 2-CBA the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It indicates that these compounds are not a sufficient carbon source. It is known that an additional carbon source may enhance the degradation capability of the strain by increasing the biomass (Zhong et al 2007 ; Zhang et al 2009 ). Quintana et al ( 2005 ) observed the intensification of naproxen and ibuprofen degradation by active sludge in the presence of powdered milk used as a growth substrate.…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that these compounds are not a sufficient carbon source. It is known that an additional carbon source may enhance the degradation capability of the strain by increasing the biomass (Zhong et al 2007 ; Zhang et al 2009 ). Quintana et al ( 2005 ) observed the intensification of naproxen and ibuprofen degradation by active sludge in the presence of powdered milk used as a growth substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorobenzoic acids, formed at the end of the known upper bph pathway, are generally further transformed very slowly by PCB-degrading bacteria, making this step a rate limiting stage in the overall PCB-biodegradation (Zhang et al, 2009). Based on some of the identified TPs (e.g.…”
Section: A Existence Of Regular Pathway Leading To Chlorobenzoic Acid...mentioning
confidence: 99%
“…Studies have clearly shown that Bph enzymes are very sensitive targets of inhibition by specific chlorinated TPs (e.g. chlorinated dihydroxybiphenyls -inhibiting BphB, chlorocatechols -inhibiting BphC chlorinated HOPDAs and benzoic acids -inhibiting BphD) Zhang et al, 2009) that could trigger the activation of alternative biodegrading pathways. Since the identified chlorobenzoic acids suggested a full functionality of the upper bph pathway, we propose that the chlorobenzoic acids that started to accumulate in the growth medium were the trigger leading to the activation of this alternative pathway.…”
mentioning
confidence: 99%
“…3-chlorobenzoic acid (3-CBA) is also applied in industry as a raw material for fabrication of dyes, pharmaceutical preparations and fungicides and as a preserving agent for adhesive and dye. This compound can accumulate in the environment as a result of co-metabolism of polychlorobiphenyls and chlorotoluenes [2,3] and water chlorination. 3-CBA is, therefore, detected in industrial wastewaters, rivers and underground water [4].…”
Section: Introductionmentioning
confidence: 99%